An Improved Mosfet Neutral-Point-Clamped Full-Bridge Transformerless Inverter for High Efficiency Distributed Photovoltaic System - Freddy Tan Kheng Suan, Ahmad Syed, Tara Kalayani Sandipamu (International Journal of Advanced Science and Technology, 2020)
Transformerless inverters are widely used in grid connected photo-voltaic (PV) distributed system due to reduced size, weight, low-cost and have mainly higher conversion efficiency. But the problems related to the galvanic isolation between the PV strings to the grid, which results dangerous leakage current is generated via parasitic parameters. Many topologies have been investigated based on the elimination of the leakage current with constant common-mode- voltage (CMV). However, neutral-point-clamped (NPC) inverter is the most efficient way for the complete elimination of the leakage current. Recently, MNPC topology has been proposed with low leakage current and high-efficiency. Based on that, here an improved MOSFET neutral-point-clamped (I-MNPC) transformerless photo-voltaic inverter (TPVI) and corresponding control strategy is proposed without sacrificing the overall performance of the PV system. It consists of seven switches and three diodes with a constant common-mode-voltage (CMV) and complete elimination of the leakage current. The performance characteristics of the proposed I-MNPC topology are similar to the M-NPC topology except in the converter structure and efficiency.The operating modes and common-mode behaviour of the I-MNPC are examined in detail.The theoretical findings of the proposed I-MNPC are verified through the Matlab / Simulink environment. Finally, the performance of the proposed I-MNPC inverter in terms of leakage current, CMV and number of components are compared with other well-known non-NPC and NPC inverter topologies.